KOMUNITAS IKAN PADANG LAMUN DI PERAIRAN PULAU KEDINDINGAN KOTA BONTANG KALIMANTAN TIMUR - Dhevy Widyawati; Aditya Irawan; Lily Inderia Sari (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, Mulawarman University, 2022)
This research was conducted in May 2021 – January 2022. This study aims to determine the Seagrass Fish Community in the waters of Kewallan Island, Bontang City, East Kalimantan. Based on sampling, it was repeated three times at 1 station. Analysis of fish data from research results using species composition (Ks), diversity index (H’), uniformity index (E) and dominance index (C). The results of the study found 775 individual fish from 28 species. Pentapodus bifasciatus is a common species with a relative abundance of (37.68%). Physical - chemical parameters consisting of temperature, turbidity, salinity, brightness, current speed, pH, DO, nitrate and phosphate are classified as very good for organisms that live in these waters. At the research station, six types of seagrass were found, namely Thalassia hemprichii, Halopila ovalis, Halopila minor, Enhalus acoroides, Syringodium isoetifolium, Cymodocea rotundata.